2009
DOI: 10.1007/s00296-009-1079-0
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B, DR and DQ antigens polymorphism in Tunisian patients with ankylosing spondylitis (a case–control study)

Abstract: The objective of the study is to assess the distribution of HLA-B genes, HLA-B27 subtypes, HLA-DRB1 and HLA-DQB1 alleles in patients with ankylosing spondylitis (AS) and in control subjects in the Tunisian population and to compare their distribution with that found in other countries. This is a case-control study that included 100 consecutive patients (85 males/15 females) with AS according to the modified New York criteria and 100 control individuals. HLA-B, B27 subtypes and class II (DR and DQ) typing of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
4
12
1
1
Order By: Relevance
“…HLA‐B27 prevalence was low in healthy controls (3%), and only 6 alleles were found to be positive: 4 HLA‐B*2705 and 2 HLA‐B*2702 variants. Similar results have been reported by Kchir et al in Tunisian population, who studied 100 AS patients and 100 controls, and detected 8 HLA‐B27 subtypes in AS patients group (the most frequent were B*2705 and B*2702 ) and 3 HLA‐B27 alleles among 100 controls . Recently, Amribet et al identified only four HLA‐B*27 variants: B*2705, B*2702 , B*2703 , and B*2708 , among which B*2705 and B*2702 were the most frequent subtypes, in 54 Moroccan AS patients positive for B*27 .…”
Section: Discussionsupporting
confidence: 86%
“…HLA‐B27 prevalence was low in healthy controls (3%), and only 6 alleles were found to be positive: 4 HLA‐B*2705 and 2 HLA‐B*2702 variants. Similar results have been reported by Kchir et al in Tunisian population, who studied 100 AS patients and 100 controls, and detected 8 HLA‐B27 subtypes in AS patients group (the most frequent were B*2705 and B*2702 ) and 3 HLA‐B27 alleles among 100 controls . Recently, Amribet et al identified only four HLA‐B*27 variants: B*2705, B*2702 , B*2703 , and B*2708 , among which B*2705 and B*2702 were the most frequent subtypes, in 54 Moroccan AS patients positive for B*27 .…”
Section: Discussionsupporting
confidence: 86%
“…B27/C*01 and B27/C*02 in Caucasian populations , B*27:05/C*02:022 and B*27:02/C*02:022 in Mexican, Spanish and Tunisian populations which reinforce our own results. Associations regarding HLA‐DRB1 and ‐DQB1 haplotypes are limited, however, B27/DRB1*11/DQB1*03 in the Tunisian population and B27/DRB1*07 in the British population have been reported . In these cases, the results were not in accordance with the significant haplotype identified by us.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding has been supported by the results obtained in different ethnic groups (Brown, et al, 1998a;Jaakkola, et al, 2006;Kchir, et al, 2010;Mahfoudh, et al, 2011;Ploski, et al, 1995;SaidNahal, et al, 2002;Sims, A M, et al, 2007). HLA-DRB1 was found to have a strong association with AS.…”
Section: Introductionsupporting
confidence: 57%
“…Within the same population, a casecontrol study reported a significant increase in HLA-DRB1*11 frequency among patients. It was also found a possible protective effect of HLA-DRB1*13 (Kchir, et al, 2010). DPA1*02:01, DPB1*13:01.…”
Section: Introductionmentioning
confidence: 87%